The Sphere : An illustrated Newspaper for the Home (voortgezet als: The Sphere : The Empire's Illustrated Weekly) - Shorter, Clement (Londen : Clement Shorter, 1900)
The Sphere: An Illustrated Newspaper for the Home and, later, The Sphere: The Empire's Illustrated Weekly, was a British newspaper, published by London Illustrated Newspapers weekly from 27 January 1900 until the closure of the paper on 27 June 1964 (Wikipedia)
Https://en.wikipedia.org/wiki/The_Sphere_(newspaper)
Online: https://catalog.hathitrust.org/Record/100692983 (met login beperkte toegang)
Engels
Krant, nieuwsbulletin